Pengaruh Brand Awareness dan Word Of Mouth Terhadap Keputusan Pembelian Produk Royco Pada Konsumen Rumah Tangga di Kota Bekasi - Bayu Indra Putera Batara; Dewi Nurbaiti; Edwin Sholeh Rahmanullah (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This study aimed to examine the influence of brand awareness and word of mouth on the purchasing decisions of Royco products among household consumers in Bekasi City. A quantitative approach was employed using a survey method by distributing questionnaires to 110 respondents, all of whom were household consumers in Bekasi. The results indicated that, partially, brand awareness has a positive and significant influence on purchasing decisions, with a significance value of 0.010. Word of mouth also had a positive and significant influence on purchasing decisions, with a significance value of 0.000. Simultaneously, both variables significantly influenced purchasing decisions, with an F-statistic value of 27.866 and a significance value of 0.000. The coefficient of determination (R Square) was 0.342, indicating that 34.2% of the variation in purchasing decisions can be explained by brand awareness and word of mouth. It can therefore be concluded that both brand awareness and word of mouth play a significant role in influencing consumer purchasing decisions for Royco products. Keywords: Brand Awareness, Word Of Mouth, Purchasing Decisions, Consumers, Households